Argumentasi Nabi Muhammad dalam Menghadapi Serangan Yahudi: Sebuah Pendekatan Retoris - Aris Kristianto; Achmad Al Farisi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to examine the challenges faced by Islamic dawah in a contemporary context, particularly in responding to arguments that attempt to undermine fundamental Islamic teachings, including concepts of divinity and prophethood. This issue aligns with the challenges encountered by Prophet Muhammad during his mission in Medina, especially in addressing the arguments presented by the Jewish community. Understanding how Allah and Prophet Muhammad provided counterarguments and refutations against these claims can offer valuable guidance for contemporary dawah efforts. The methodology employed in this research is a literature review with a descriptive analysis approach. The data sources consist of relevant verses from the Qur'an and historical accounts that document the rebuttals made against the Jews. This study analyzes the structure of the arguments utilized by Allah and Prophet Muhammad, applying the theory of refutational argumentation along with various methods of argument rejection. The findings reveal that Allah and Prophet Muhammad effectively countered the arguments posed by the Jews by providing logical evidence and addressing ad hominem attacks directed at the Prophet and the Muslim community. They employed parallel reasoning to reverse the accusations made against them, as well as using negative labeling as a response to the ad hominem critiques aimed at the Muslim community. These findings are expected to provide valuable insights for facing the challenges of dawah in the present day.